Inflammation severity, rather than respiratory failure, is strongly associated with mortality of ARDS patients in high-altitude ICUs - Molano-Franco, Daniel; Masclans Enviz, Joan Ramon; Viruez-Soto, Antonio; Gomez, Mario; Rojas, Harvey; Beltran, Edgar; Nieto, Victor; Aliaga-Raduan, Fernanda; Iturri, Pablo; Arias-Reyes, Christian; Soliz, Jorge (Frontiers in Physiology, 2025)
IntroductionIn high-altitude cities located above 2,500 m, hospitals face a concerning mortality rate of over 50% among intensive care unit (ICU) patients with acute respiratory distress syndrome (ARDS). This elevated mortality rate is largely due to the absence of altitude-specific medical protocols that consider the unique physiological adaptations of high-altitude residents to hypoxic conditions. This study addresses this critical gap by analyzing demographic, clinical, sex-specific, and preclinical data from ICUs in Bogotá, Colombia (2,650 m) and El Alto, Bolivia (4,150 m).MethodsA cohort of seventy ARDS patients, aged 18 and older, was evaluated within 24 h of ICU admission. Data collected included demographic information (age, sex), clinical characteristics (primary pathology, weight, height), vital signs, respiratory variables, cardiorespiratory parameters, blood count results, inflammatory markers, severity assessment scores, and comorbidities. Advanced statistical analyses, such as multivariate logistic regression and principal component analysis, were utilized to identify key clinical predictors of ARDS-related mortality.ResultsOur findings indicate that in high-altitude ICUs, monitoring inflammatory markers may be more beneficial for improving ARDS survival rates than emphasizing respiratory failure markers. Unexpectedly, we found no significant differences in clinical outcomes between altitudes of 2,650 and 4,150 m or between male and female patients.ConclusionThe study concludes that, in high-altitude settings, ARDS patient survival in ICUs is more closely associated with managing inflammatory responses than with focusing solely on respiratory parameters. Further large-scale studies are recommended to validate the impact of inflammatory marker monitoring on survival outcomes in high-altitude ICUs.